Strategy Building for Dealing with COVID-19 in Urban Transportation Development in Jakarta - Irmawandari; Andri N.R. Mardiah; Suryani Eka Wijaya (Amcolabora, 2022)
One of the impacts affected by the existence of the Large Scale Social Restriction Policy in Jakarta is the urban transportation sector, according to data from ppid.Transjakarta, which states that there has been a decrease in Transjakarta and Jaklingko 2020 users by 33.8% of the data on the number of Transjakarta and Jaklingko users in Jakarta in 2019 for the period of March –July. However, the dependence of urban communities on public transportation in carrying out their activities during the COVID-19 pandemic has the potential for the spread of COVID-19 cases. This article aims to develop a strategy for urban transportation development in the COVID-19 era in Jakarta. Input this research results on internal and external factors in the form of strengths, weaknesses, opportunities, and threats in the development of transportation for the COVID-19 era in Jakarta is based on interviews with key stakeholders using the content analysis method and the second stage is in formulating the right strategy using SWOT analysis. The research results show that six alternative strategies can be applied in the development strategy of urban transportation in the COVID-19 era in Jakarta.